2017
DOI: 10.1007/s10237-017-0909-3
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to radial expansion limits muscle strain and work

Abstract: The collagenous extracellular matrix (ECM) of skeletal muscle functions to transmit force, protect sensitive structures, and generate passive tension to resist stretch. The mechanical properties of the ECM change with age, atrophy, and neuromuscular pathologies, resulting in an increase in the relative amount of collagen and an increase in stiffness. Although numerous studies have focused on the effect of muscle fibrosis on passive muscle stiffness, few have examined how these structural changes may compromise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 57 publications
(102 reference statements)
0
66
0
Order By: Relevance
“…In univariate analysis, several SR parameters were significantly correlated with force, confirming that both normal and shear SRs significantly predict muscle force output. It is also noteworthy that, in multivariable regression, the two significant predictors of force in a cohort of young and senior subjects are SR indices SR cc and SR fc _max ; both are known from other studies to be related to the status of the ECM …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In univariate analysis, several SR parameters were significantly correlated with force, confirming that both normal and shear SRs significantly predict muscle force output. It is also noteworthy that, in multivariable regression, the two significant predictors of force in a cohort of young and senior subjects are SR indices SR cc and SR fc _max ; both are known from other studies to be related to the status of the ECM …”
Section: Discussionmentioning
confidence: 98%
“…The results of the SR analysis in the principal basis and in the fiber basis show that normal strains along the fiber (SR fiber and SR ff ) and in the fiber cross‐section (SR in‐plane ) are significantly lower in the aging cohort. Azizi et al showed by combining a mathematical model with experimental manipulation that the structural changes in the ECM (eg, increase in collagen and in stiffness) compromise the muscle's ability to expand radially, which in turn restricts muscle shortening . Thus, the observed changes in both normal strains (along the fiber as well as in the fiber cross‐section) can be attributed, at least in part, to the structural changes in the ECM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Independent of changes in collagen content, mechanical unloading also disrupts the normal three‐dimensional arrangement of collagen fibres in the skeletal muscle. In normal orientation, collagen fibres are either running parallel to the muscle fibres preventing over‐elongation and over‐contraction, or run perpendicular to the muscle fibres connecting adjacent muscle fibres in the motor unit . Unloading disturbs this regular orientation of collagen fibres and causes a relative increase in the number of longitudinally and perpendicularly placed collagen fibres, which are likely to hamper force development during muscle contraction.…”
Section: Methodsmentioning
confidence: 99%